A Fifth-Order Accurate Weighted ENN Difference Scheme and Its Applications (Journal of Computational Mathematics, 2001)
In this paper, we have constructed a high accurate difference scheme based on the ENN scheme [1]. The new scheme has 5th-order accuracy in smooth regions and can keep the essentially non-oscillatory property.
Keywords: ENN scheme; WENO scheme; Shock-boundary-layer interaction.